Rheological evaluation of bituminous binder modified with waste plastic material - Abdelaziz, Mahrez; Mohamed Rehan, Karim (2010)

(untitled)
This research investigates the viscelastic properties of asphalt bitumen modified with waste plastic bottles compared to the ordinary 80/100 bitumen. The contents of modifier will be varied to investigate its effects on the rheological properties of the modified binders. The binders were characterized using standard laboratory tests such as penetration test, softening point test, viscosity test and dynamic shear rheometer test. Using the waste plastic materials showed prominent results in improving the viscoelstic properties of ordinary bitumen. The effects waste modifiers influenced significantly the rheological behavior of bitumen by increasing its complex modulus and decreasing phase angle.